INVESTIGATION OF ANIONIC POLYMERIZATION OF ACRYLAMIDE MONOMERS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
It was found that M,M-diethanolacrylamide and M,M-diethanol(met)acrylamide does not react with anionic polymerization; the reasons for this behavior of these monomers have been identified. It is shown that the products of anionic polymerization of acrimides are hyperbranched copolymers containing fragments of heterocain and carbocain structures. Macromolecules have amide and acrylamide groups as end groups; terminal tert-butoxide groups from the polymerization initiator used have been found in some macromolecules. The glass transition and melting temperatures of the anionic polymerization products of the studied acrylamide monomers were measured.